Implementasi Pendidikan Karakter Mandiri Melalui Keteladanan Dan Pembiasaan Pada Siswa Kelas IV Sekolah Dasar Negeri 1 Baturan Kecamatan Gantiwarno Kabupaten Klaten - Sarjana, Gatot (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to describe the implementation of independent character education through exemplary and habituation in class IV students of Elementary School 1 Baturan. Based on the background of the problem and initial observations and interviews with the class IV teacher, The method used in this study is descriptive qualitative method supported by field research and references related to the themes discussed. The subjects used in this study were fourth grade students, totaling 11 students. Data collection techniques used by using the method of observation, interviews, and documentation methods. Qualitative data analysis techniques use reduction, display and generalizations or conclusions.Based on the results of the research, it shows that (1) the reasons for carrying out independent character education for students include (2) the implementation of students' independent character education can be seen from the aspect of self- development; (3) Exemplary forms and habits that are implemented